The Influence of E-WOM on Facebook Social Media on Purchase Decition with Purchase Intention as a Mediation Variable - Solikhatun, Is; Rahayu, Teguh Imam; Ridwan, Ali (Journal of Economics and Social Sciences (JESS), 2025)
Small and medium-sized enterprises (SMEs), such as the producer of Bakso Balungan Mak Jah in Tempuran Village, Demak, are increasingly using social media as a key strategy in the digital era. This study aims to analyze the influence of electronic word of mouth (e-WOM) on consumer purchase decisions by considering the mediating role of purchase intention. A quantitative method is used in this research, employing the Structural Equation Modeling Partial Least Squares (SEM-PLS) approach, supported by SmartPLS version 3.2.9. Data were collected from 100 individuals who actively use Facebook. The analysis results show that e-WOM significantly affects both purchase intention and purchase decision. Furthermore, purchase intention partially mediates the influence of e-WOM on purchase decision. The findings indicate that credible and positive online reviews can enhance consumers’ desire to purchase and support better decision-making. This study offers practical recommendations for digital marketing strategies for local SMEs and highlights the importance of managing online reputation.